Global Research Trends and Intellectual Structure of Academic Burnout Among College Students: A Bibliometric Analysis (2010–2026) - M. Amien Mujaddid; Wahyu Budi Nugraha Budi Nugraha; Basir Jarah Anilon; Ahmad T.Zainal Abidin; Alfurqaan Hakiki; Fauzi Rochman (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
Academic burnout has received increasing attention in higher education research due to rising academic demands, digital transformation, and growing concerns about student mental health. Despite the rapid expansion of the literature, no bibliometric study has comprehensively mapped the intellectual structure, thematic evolution, and developmental trajectory of academic burnout research specifically among college students. This study addresses this gap by conducting a bibliometric analysis of 359 Scopus-indexed articles published between 2010 and 2026. Data were analyzed using VOSviewer and Biblioshiny through keyword co-occurrence, co-citation, bibliographic coupling, collaboration network, and thematic evolution analyses. The findings reveal a substantial increase in publication output, rising from two articles in 2010 to 95 articles in 2025. China, Indonesia, and Iran emerged as the most productive contributing countries, while the intellectual foundations of the field remain strongly influenced by the seminal works of Maslach, Leiter, and Schaufeli. Thematic analysis identified four developmental phases of the field: Emergence (2010–2014), Early Growth (2015–2018), Acceleration (2019–2021), and Exponential Surge (2022–2025). Furthermore, digital-related themes, including technostress, smartphone addiction, and social media fatigue, have become increasingly prominent in recent studies. This study contributes theoretically by identifying a digital-burnout nexus within the extended Job Demands-Resources (JD-R) framework and methodologically by demonstrating the value of a multi-indicator bibliometric approach. The findings provide a foundation for future research and evidence-based interventions aimed at promoting student well-being in increasingly digitalized higher education environments.